1975
DOI: 10.1172/jci108231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexamethasone on insulin binding, glucose transport, and glucose oxidation of isolated rat adipocytes.

Abstract: A B S T R A C T We have studied the in vitro effects of dexamethasone on isolated rat adipocytes at concentrations of dexamethasone therapeutically achieved in man. Glucose oxidation, glucose transport, and insulin binding were assessed. In dexamethasone-treated cells, glucose oxidation was decreased by 30-40% both in the absence of insulin (basal state) and at low insulin levels (less than 25 AsU/ml). At maximally effective insulin levels (over 100 F'U/ml) no differences existed between control and treated ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
128
3
1

Year Published

1985
1985
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(152 citation statements)
references
References 37 publications
20
128
3
1
Order By: Relevance
“…Insulin action on target tissues might be altered by a decreased receptor number and/or affinity, or by a post-receptor defect [13,14]. Changes in the levels of counterregulatory hormones could also be involved, e. g. glucagon stimulates insulin-inhibited hepatic glucose production [14].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin action on target tissues might be altered by a decreased receptor number and/or affinity, or by a post-receptor defect [13,14]. Changes in the levels of counterregulatory hormones could also be involved, e. g. glucagon stimulates insulin-inhibited hepatic glucose production [14].…”
Section: Discussionmentioning
confidence: 99%
“…Epididymal adipose tissue was removed from 5-week-old male Sprague-Dawley rats and digested with collagenase type II (1 mg/ml; Sigma Chemical, St. Louis, MO, USA) in 1 ml Krebs-Ringer HEPES (KRH) buffer (131 mmol/l NaCl, 4.7 mmol/l KCl, 2.5 mmol/l CaCl 2 , 1.25 mmol/l MgCl 2 , 2.5 mmol/l NaH 2 PO 4 , 10 mmol/l HEPES, pH 7.4) supplemented with 1% BSA and 2 mmol/l pyruvate for 1 h at 37°C [16]. After digestion, adipocytes were prepared as described previously [17].…”
Section: Isolation Of Epididymal Adipocytesmentioning
confidence: 99%
“…Diabetes 49:1700-1708, 2000 R esearch has shown that glucocorticoids are hormones that induce insulin resistance and that their clinical use often exacerbates diabetes (1)(2)(3). This glucocorticoid-induced insulin resistance has been demonstrated not only in clinical cases but also in animal experiments (4,5) and in vitro experiments using isolated or cultured cells (6)(7)(8). For example, in skeletal muscle of glucocorticoid-treated rats, increases in glucose uptake induced by insulin, IGF-I, or hypoxia were found to be decreased (9,10).…”
mentioning
confidence: 99%